From Classic Securities to Dematerialised Financial Instruments – Evolution and Perspective - Horosz, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
Focusing mainly on historical issues, the article presents the process by which securities admitted to public trading in the 1990s (with the total dematerialisation of public trade) led to fully dematerialised securities, which are one of the types of financial instruments sold on the regulated market. The author also identifies trends he believes could lead to the full dematerialisation of all types of securities, the abandonment of the notion of securities as a financial instrument, and the sale of such dematerialised financial instruments directly between interested parties via web portals, bypassing stock exchanges and brokerage houses.